A lanthanide-loaded molecular sieve composite nanofiber material and its preparation method and application

By combining ZSM-5 molecular sieve with nanofiber membranes and loading lanthanide metal elements, the agglomeration and recycling problems of rare earth compounds when treating phosphorus-containing wastewater are solved, and the effects of efficient adsorption and low-cost production are achieved.

CN118854663BActive Publication Date: 2025-02-14BEIJING NORMAL UNIV AT ZHUHAI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410896767.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-05
Publication Date
2025-02-14
Estimated Expiration
2044-07-05

AI Technical Summary

Technical Problem

Existing rare earth compounds are prone to agglomeration when treating phosphorus-containing wastewater, resulting in low adsorption efficiency, difficulty in recycling and rare earth erosion, and the production process is complex and costly.

Method used

By combining ZSM-5 molecular sieve with nanofiber membranes and loading lanthanide metal elements by hydrothermal synthesis, lanthanide-loaded molecular sieve composite nanofiber materials were prepared to avoid agglomeration and enhance the mechanical strength and recovery efficiency of the adsorbent.

Benefits of technology

It improves the adsorption efficiency and recovery efficiency of lanthanide compounds, reduces the loss of rare earths, reduces production costs, and enhances the mechanical strength and stability of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118854663B_ABST
    Figure CN118854663B_ABST
Patent Text Reader

Abstract

The present invention discloses a lanthanide-loaded molecular sieve composite nanofiber material and its preparation method and application, belonging to the technical field of composite materials, the present invention combines ZSM-5 molecular sieve with composite nanofiber material, and loads rare earth metal element lanthanum, and exerts the advantages of molecular sieve membrane high temperature resistance, chemical corrosion resistance, good mechanical stability, non-flammability and long service life, uniform pore size, high specific surface area and adjustable chemical properties. The molecular sieve composite nanofiber material prepared by the present invention has a higher porosity, a unique three-dimensional network structure and a uniform distribution of molecular sieves, which can not only give play to the advantages of molecular sieves in the field of industrial applications, but also reflect the advantages of composite nanofiber materials in fixed bed reaction processes. There is a strong interaction force between the molecular sieve and the carrier, which solves the problem of particle leaching, and the molecular sieve is more evenly distributed at the same time, so its use efficiency and service life can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite materials, and in particular relates to a lanthanide-loaded molecular sieve composite nanofiber material and a preparation method and application thereof. Background Art

[0002] Phosphate is a key factor leading to eutrophication of water bodies, mainly appearing in freshwater bodies. The deterioration of water quality may affect the water supply of residents, and in serious cases, even threaten the safety of drinking water. How to efficiently purify phosphorus-containing wastewater, use economical and effective technical means to repair phosphorus-contaminated water bodies, and avoid the occurrence of eutrophication is of great practical significance to ecological protection, economic development and social progress.

[0003] The most commonly used method for treating phosphorus-containing wastewater and remediating phosphorus-contaminated water bodies is adsorption (Chem. Eng. J. 372 (2019) 241-250), and the choice of adsorbent is a very critical factor. At present, a series of studies have shown that rare earth compounds have good potential for environmental remediation applications (Water Research, 2016, 88, 852-860), but the problems they have limited their development, such as complex production processes, high costs and difficulty in large-scale production. The most commonly used rare earth element as an adsorbent is lanthanum. Although lanthanide compounds often have good adsorption capacity for phosphorus, due to the small particle size of nano-scale lanthanide compounds, agglomeration often occurs during use. At the same time, the small particle size also makes it difficult to recover the adsorbent after use, requiring additional separation steps, increasing the difficulty and cost of operation, and causing the loss of lanthanide compounds to be inevitable (Colloids & Surfaces A: Physicochemical & Engineering Aspects. 2007, 308 (1): 47-53).

[0004] The rare earth metal compounds are uniformly loaded onto different carriers to avoid the occurrence of agglomeration, increase the contact efficiency between the adsorbent and the pollutants in the water, and are easy to separate, improve the recovery efficiency, and reduce the loss of rare earth compounds. However, how to select a carrier material with high stability, physical strength and excellent environmental tolerance is a problem that people need to solve.

[0005] Molecular sieves have uniform pore distribution, large specific surface area, good mechanical strength and chemical stability, and abundant active center sites, making them an excellent carrier material. However, molecular sieves are mostly granular substances, and the bed pressure in a fixed bed reactor is relatively high. In addition, their particle size is small, and they are easy to disperse after the reaction but difficult to collect, making it difficult to meet the needs of actual production. Summary of the invention

[0006] In order to solve the above technical problems, the present invention proposes a lanthanide-loaded molecular sieve composite nanofiber material and its preparation method and application. The present invention combines molecular sieve with nanofiber membrane for the first time to prepare molecular sieve composite nanofiber membrane as a carrier for water treatment. There are many materials that can be used to prepare nanofiber membranes, among which polyacrylonitrile (PAN) has good hydrothermal stability, low cost and no pollution to the environment. Polyacrylonitrile nanofiber membrane has excellent properties such as high porosity and high permeability, and can be used in many fields such as dye adsorption, filtration, heavy metal ion adsorption, etc.

[0007] To achieve the above object, the present invention provides the following technical solutions:

[0008] One of the technical solutions of the present invention:

[0009] The present invention provides a method for preparing a lanthanide-loaded molecular sieve composite nanofiber material, comprising the following steps:

[0010] (1) mixing polyacrylonitrile and N,N-dimethylacetamide to prepare a nanofiber composite material precursor solution;

[0011] (2) stirring the nanofiber composite material precursor solution and then ultrasonicating it to obtain a nanofiber composite material carrier solution;

[0012] (3) obtaining a nanofiber composite material carrier by electrospinning and drying;

[0013] (4) calcining the dried nanofiber composite material carrier in an air atmosphere, soaking and modifying the calcined nanofiber composite material carrier with a cationic polymer solution, and washing with ammonia water;

[0014] (5) placing the nanofiber composite material carrier washed with ammonia water in a seed solution and immersing it, and then washing it with ammonia water;

[0015] (6) mixing the material obtained in step (5) with a secondary growth liquid for crystallization, rapidly cooling with water after the crystallization is completed, and obtaining a molecular sieve composite nanofiber material by washing, drying and calcining;

[0016] (7) immersing the molecular sieve composite nanofiber material in an alkaline solution, then washing it by shaking, and drying it to obtain a pretreated molecular sieve composite nanofiber material;

[0017] (8) The pretreated molecular sieve composite nanofiber material is mixed with a lanthanum nitrate (La(NO3)3) solution, subjected to oscillation reaction under constant temperature conditions, urea is added, and the lanthanum-loaded molecular sieve composite nanofiber material is obtained by a hydrothermal synthesis method.

[0018] Preferably, in step (1), the mass volume ratio of polyacrylonitrile and N,N-dimethylacetamide is (5-20) g:100 mL.

[0019] Preferably, in step (2), the stirring rate is 100 to 300 rpm, and the time is 4 to 10 hours;

[0020] The ultrasonic time is 20 to 60 minutes.

[0021] Preferably, in step (3), the electrospinning conditions are: voltage of 6 to 15 kV, solution flow rate of 0.05 to 0.5 mm / min, and the distance between the needle and the receiver of 3 to 10 cm;

[0022] The drying is freeze-drying under vacuum for 8 to 12 hours.

[0023] Preferably, in step (4), the calcination temperature is 400-600° C., and the calcination time is 3-8 hours;

[0024] The cationic polymer solution is a polyhydroxypropyl dimethyl ammonium chloride solution, and its concentration is 0.1-1 wt %;

[0025] The soaking time is 10 to 60 minutes;

[0026] The concentration of the ammonia water is 0.05-0.5 mol / L, and the number of cleaning times is 2-5 times.

[0027] Preferably, in step (5), the seed solution is prepared by mixing TEOS, TPAOH, H2O and EtOH in a molar ratio of 1:0.36:(10-40):(0-8) to obtain the seed solution, wherein the molar number of EtOH is not 0;

[0028] The soaking time is 1h;

[0029] The concentration of the ammonia water is 0.05-0.5 mol / L, and the number of cleaning times is 2-5 times.

[0030] Preferably, in step (6), the secondary growth solution is prepared by mixing SiO2, TPAOH, Al2O3 and H2O in a molar ratio of 1:0.112:(0-0.118):111 to obtain the secondary growth solution, wherein the molar number of Al2O3 is not 0;

[0031] The crystallization temperature is 50-200°C;

[0032] The rapid water cooling is to use deionized water to rapidly cool the reactor;

[0033] The cleaning is to use deionized water to wash the molecular sieve composite nanofiber material until its pH is 6-8;

[0034] The calcination temperature is 300-1000°C, the holding time is 2-6h, and the heating rate and cooling rate are both 0.5-2°C / min;

[0035] The drying temperature is 50-200°C.

[0036] Preferably, in step (7), the alkaline solution is NaOH solution, KOH solution or Ca(OH)2 solution;

[0037] The oscillation condition is oscillating at 50°C to 100°C for 12h to 36h; if there is no oscillator, it can be left to stand;

[0038] The drying is freeze-drying under vacuum for 8 to 12 hours.

[0039] Preferably, in step (8), the concentration of the La(NO3)3 solution is 0.1 to 5 mol / L;

[0040] The molar ratio of urea to lanthanum in the lanthanum nitrate solution is (60-100):1;

[0041] The oscillation condition is oscillating at 50°C to 100°C for 12h to 36h; if there is no oscillator, it can be left to stand;

[0042] The reaction conditions of the hydrothermal synthesis method are 50°C to 100°C and oscillation for 8h to 24h; if there is no oscillator, it can be left to stand;

[0043] The drying is carried out at a low temperature of 40 to 60° C. for 8 to 12 hours.

[0044] The present invention combines ZSM-5 molecular sieve with composite nanofiber material and loads rare earth metal element lanthanum, so as to give full play to the advantages of molecular sieve membrane such as high temperature resistance, chemical corrosion resistance, good mechanical stability, non-flammability and long service life, and at the same time give full play to its advantages such as uniform pore size, high specific surface area and adjustable chemical properties. The molecular sieve composite nanofiber material prepared by the present invention has high porosity, unique three-dimensional network structure and uniform molecular sieve distribution, which can not only give full play to the advantages of molecular sieve in the field of industrial application, but also reflect the advantages of composite nanofiber material in fixed bed reaction process. At the same time, in the present invention, the molecular sieve is directly synthesized on the surface of the nanofiber carrier, and there is a strong interaction force between the molecular sieve and the carrier. At the same time, the molecular sieve is more evenly distributed, so its use efficiency and service life can be effectively improved. At the same time, lanthanum is loaded on the molecular sieve composite nanofiber material, which avoids the generation of agglomeration phenomenon, solves the problem of easy leaching of particles, and the metal loss rate after the reaction is less than 0.05%, which increases the contact efficiency between the adsorbent and the pollutants in the water body, and at the same time improves the mechanical strength of the adsorbent, is easy to separate, improves the recovery efficiency, and reduces the loss of rare earth compounds. In summary, the composite material of the present invention has very good reaction performance and practical application ability.

[0045] The second technical solution of the present invention:

[0046] The present invention also provides a lanthanide-loaded molecular sieve composite nanofiber material prepared by the method.

[0047] The lanthanide-loaded molecular sieve composite nanofiber material of the present invention has adjustable pore size, uniform structure, high load, easy preparation, ideal mechanical strength, strong interaction between molecular sieve and nanofiber carrier, and can be applied to fixed bed adsorbent to simultaneously exert the advantages of molecular sieve and nanofiber composite material, which can significantly reduce bed resistance, increase mass transfer and heat transfer efficiency and contact efficiency, thereby improving adsorption efficiency, and can evenly distribute molecular sieve on the carrier, and reduce leaching loss of metal in the reaction. At the same time, the three-dimensional network structure can greatly eliminate channel flow, back-mixing phenomenon and radial diffusion limitation, etc., and improve adsorption efficiency.

[0048] The third technical solution of the present invention:

[0049] The present invention also provides application of the lanthanide-loaded molecular sieve composite nanofiber material in a fixed bed adsorbent.

[0050] The lanthanide-loaded molecular sieve composite nanofiber material of the present invention can be used as a fixed bed adsorbent, and the fixed bed adsorbent is used to adsorb organic matter, and the organic matter is preferably phosphate and its derivatives, and more preferably phosphate.

[0051] The lanthanide-loaded molecular sieve composite nanofiber material of the present invention can be used as a fixed bed adsorbent, especially a fixed bed adsorbent for wastewater treatment. When used as a fixed bed adsorbent, compared with a traditional fixed bed adsorbent, the use of the lanthanide-loaded molecular sieve composite nanofiber material of the present invention can reduce the pressure drop of the fixed bed layer, and at the same time, the adsorption rate and adsorption efficiency are improved to a certain extent, and when used for liquid phase reaction, the molecular sieve will not be leached and lost.

[0052] The present invention combines molecular sieve with nanofiber membrane for the first time, and loads rare earth metal lanthanum through hydrothermal synthesis, thereby solving the shortcomings of lanthanide compounds being easy to agglomerate, having low mechanical strength, and being difficult to recycle. Moreover, by using molecular sieve composite nanofiber materials, compared with simple molecular sieves, the molecular sieve can be formed into a membrane while maintaining its activity, thereby reducing its bed resistance in a fixed bed reactor, while combining the properties of molecular sieves such as large specific surface area, uniform pore size, ion exchangeability, selective adsorption, and adjustable hydrophilicity and hydrophobicity, the advantages of fiber membranes such as high specific surface area, uniform thickness, high porosity, and adjustable structure are brought into play, giving full play to the excellent performance of each component of the composite material, thereby enhancing its practical application ability and improving the practical value of the adsorbent.

[0053] The present invention loads the molecular sieve onto the nano polymer fiber membrane instead of the metal fiber. The functional groups on the molecular sieve and the functional groups on the polymer fiber can produce an electron-electron effect, so that the metal lanthanum loaded on the molecular sieve can use the molecular sieve as a medium to produce a ligand-metal charge transfer (LMCT) effect with the abundant electron-rich groups in the polymer structure, strengthen the electron transfer ability, and make the electrons on the membrane exchange with the adsorbate faster and more efficiently, thereby improving the adsorption reaction efficiency. The molecular sieve of the present invention exists in the form of a molecular sieve layer, and the molecular sieves are stacked on each other to form a micro-mesoporous multi-scale structure. Compared with the particle molecular sieve having only a microporous structure, the composite nanofiber material of the present invention has a larger specific surface area and a better effect. Compared with directly loading the metal onto the polymer fiber membrane, the porous structure of the molecular sieve of the present invention can increase the adsorption active sites and also contribute to the dispersion of the metal. Therefore, using the molecular sieve as a medium, the adsorption effect of the metal on the pollutant on the membrane can be better exerted.

[0054] Compared with the prior art, the present invention has the following advantages and technical effects:

[0055] (1) The lanthanum-loaded molecular sieve composite nanofiber material of the present invention is a membrane material with more stable physical and chemical properties. The lanthanum-loaded molecular sieve composite nanofiber material of the present invention has the advantages of both nanofiber composite materials and molecular sieve materials, and has the physicochemical properties of the corresponding molecular sieve, such as large specific surface area, uniform pore size, ion exchange, selective adsorption, and adjustable hydrophilicity and hydrophobicity, as well as the advantages of high specific surface area, uniform thickness, high porosity, and adjustable structure of fiber membranes. Moreover, lanthanum is loaded on the molecular sieve composite nanofiber material to avoid the occurrence of agglomeration, increase its contact efficiency with pollutants in the water body when used as an adsorbent, and is easy to separate, improve recovery efficiency, and reduce the loss of rare earth compounds. Compared with particles, the lanthanum-loaded molecular sieve composite nanofiber material of the present invention is easier to separate and can be directly taken out from the reaction system. At the same time, it reduces the steps of filtration, centrifugation, precipitation, etc., which can greatly reduce costs and improve recovery efficiency. The recovery efficiency of the membrane can be close to 100%. In summary, the lanthanide-loaded molecular sieve composite nanofiber material of the present invention has excellent performance, low production cost, simple production method, stable product quality, flexible use, good effect, and good industrial application value;

[0056] (2) The lanthanide-loaded molecular sieve composite nanofiber material of the present invention has a higher practical utilization value. The molecular sieve in the molecular sieve composite nanofiber material of the present invention is more evenly distributed, and the molecular sieve grows evenly on the surface of the microfiber material, which can effectively improve the efficiency of the adsorption reaction. And as a macroporous material, the molecular sieve composite nanofiber material can effectively reduce the bed pressure, enhance mass transfer and heat transfer, and improve the adsorption efficiency. Moreover, the molecular sieve and the nanocomposite fiber carrier in the molecular sieve composite nanofiber material of the present invention have a strong interaction, which effectively reduces the molecular sieve leaching rate during the reaction process, facilitates recovery, and improves its ability to be put into actual production;

[0057] (3) The lanthanide-loaded molecular sieve composite nanofiber material of the present invention is more convenient to adjust its properties. Compared with simple molecular sieves, as a membrane material, its physical and chemical properties can be adjusted more easily. Not only can the length and diameter of the fiber membrane be adjusted, but also the properties of the molecular sieve can be controlled by controlling the properties of the fiber. At the same time, the porous structure of the molecular sieve can make up for the deficiencies of the fiber in adsorption performance and selectivity, promoting its actual production application. BRIEF DESCRIPTION OF THE DRAWINGS

[0058] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0059] Figure 1 This is a scanning electron microscope image of the nanofiber composite material carrier formed in Example 1;

[0060] Figure 2 This is a scanning electron microscope image of the lanthanide-loaded molecular sieve composite nanofiber material of Example 1;

[0061] Figure 3 This is a physical picture of the lanthanide-loaded molecular sieve composite nanofiber material of Example 1. DETAILED DESCRIPTION

[0062] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0063] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0064] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0065] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0066] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0067] Unless otherwise specified, the room temperature in the embodiments of the present invention is 25±2°C.

[0068] All raw materials used in the examples of the present invention are commercially available.

[0069] The technical solution of the present invention is further illustrated by the following embodiments.

[0070] Example 1

[0071] A method for preparing a lanthanide-loaded molecular sieve composite nanofiber material:

[0072] (1) Preparation of nanofiber composite carrier

[0073] (1-1) Weighing 10 g of polyacrylonitrile, measuring 100 mL of N,N-dimethylacetamide, stirring and dissolving the polyacrylonitrile in the N,N-dimethylacetamide to prepare a nanofiber composite material precursor solution;

[0074] (1-2) stirring the nanofiber composite material precursor solution at a rotation speed of 200 rpm for 6 hours, and then ultrasonically treating for 30 minutes to obtain a nanofiber composite material carrier solution;

[0075] (1-3) The nanofiber composite carrier solution was sucked by a needle tube for electrospinning. The voltage during electrospinning was +10 kV, the solution flow rate was 0.1 mm / min, and the distance between the needle and the receiver was 4 cm. After electrospinning, the membrane was freeze-dried under vacuum for 9 h to obtain a formed nanofiber composite carrier. The scanning electron micrograph is shown in Figure 1 , it can be seen that the fiber surface is smooth and there is no molecular sieve layer loading;

[0076] (2) Preparation of molecular sieve composite nanofiber materials with molecular sieve grown on the surface

[0077] (2-1) The nanofiber composite material carrier is placed in a muffle furnace and calcined at 550°C for 6 hours in an air atmosphere to form a porous oxide film on its surface. The oxidized nanofiber composite material carrier is soaked in a 0.5wt% polyhydroxypropyl dimethyl ammonium chloride solution for 30 minutes, then washed three times with 0.1mol / L ammonia water, and dried at room temperature. Subsequently, the above substances are mixed according to the molar ratio of TEOS, TPAOH, H2O and EtOH of 1:0.36:10:2 to obtain a synthetic solution, and the synthetic solution is poured into a 50mL polytetrafluoroethylene-lined stainless steel reactor and crystallized at 150°C for 24 hours; the reactor is taken out and quickly cooled with cold water, and the obtained seed solution is centrifuged and purified four times until the pH is 7 to obtain a seed crystal. The obtained seed crystals were added into deionized water to prepare a 2 wt% solution, and the pH value was adjusted to 10 with ammonia water to obtain a seed crystal solution; the carrier modified by the cationic polymer solution was placed in the seed crystal solution and soaked for 1 hour, and then the carrier after adsorbing the seed crystals was washed with 0.1 mol / L ammonia water and dried for use.

[0078] (2-2) The above substances are mixed in a molar ratio of SiO2, TPAOH, Al2O3 and H2O of 1:0.112:0.005:111 to prepare a secondary growth solution, and the secondary growth solution is poured into a 200 mL polytetrafluoroethylene-lined stainless steel reactor. The carrier after adsorbing the seed crystal is then placed vertically in the reactor and crystallized at 150°C for 24 hours. The reactor is taken out and quickly cooled with cold water. The obtained molecular sieve membrane sample is washed with deionized water, dried at 100°C, and finally heated to 500°C at a rate of 1°C / min in a muffle furnace, calcined for 4 hours, and then cooled to room temperature at the same rate to remove the organic template to obtain a ZSM-5 molecular sieve composite nanofiber material.

[0079] (3) Hydrothermal synthesis method for loading rare earth ions

[0080] (3-1) Take the ZSM-5 molecular sieve composite nanofiber material and immerse it in 2.5 mol / L NaOH solution and let it stand for 24 hours. Take it out and immerse the ZSM-5 molecular sieve composite nanofiber material in clean water, shake it for 10 minutes, take it out, rotate at 200 rpm, repeat the washing process three times, dry it with paper, and dry it at 60°C for 12 hours.

[0081] (3-2) The dried ZSM-5 molecular sieve composite nanofiber material is placed in 200mL of 0.2mol / L La(NO3)3 solution, and shaken at 80°C at 165rpm for 24h. Then, urea is added (urea:La=80:1, molar ratio, the same below). The reactor is sealed and shaken at 80°C at 165rpm for 12h. After being taken out, it is washed with clean water (the cleaning process is the same as (3-1)), and dried at 60°C to obtain a lanthanide-loaded molecular sieve composite nanofiber material.

[0082] The lanthanide-loaded molecular sieve composite nanofiber material prepared in this embodiment is a lanthanide-loaded ZSM-5 molecular sieve composite nanofiber material, and the loaded active component is lanthanum carbonate, which is used to adsorb phosphate in water. The adsorption conditions are pH = 5.5, initial phosphate concentration = 200 mg / L, temperature = 30°C, and adsorbent dosage (i.e., dosage of lanthanide-loaded molecular sieve composite nanofiber material) = 2 g / L. Under these conditions, the adsorption capacity is 86.2 mg-PO4 3- / g.

[0083] Figure 2 This is a scanning electron microscope image of the lanthanide-loaded molecular sieve composite nanofiber material of Example 1. It can be seen that the round molecular sieve particles are evenly loaded on the fiber surface to form a molecular sieve layer, and the granular lanthanum hydroxide metal particles are also successfully loaded on the molecular sieve layer; Figure 3 This is a physical picture of the lanthanide-loaded molecular sieve composite nanofiber material of Example 1, and it can be seen that the material is in a film-like shape.

[0084] The thickness of the lanthanide-loaded molecular sieve composite nanofiber material prepared in this embodiment is 1 to 2 mm. Compared with the traditional granular fixed bed adsorbent, the use of the composite material of the present invention can reduce the bed pressure drop of the fixed bed by 20% to 70%, and the adsorption efficiency is improved to a certain extent; when used for liquid phase reactions, the loss rate of the molecular sieve can be reduced to 0.

[0085] Example 2

[0086] A method for preparing a lanthanide-loaded molecular sieve composite nanofiber material:

[0087] (1) Preparation of nanofiber composite carrier

[0088] (1-1) Weighing 8 g of polyacrylonitrile, measuring 100 mL of N,N-dimethylacetamide, stirring and dissolving the polyacrylonitrile in the N,N-dimethylacetamide to prepare a nanofiber composite material precursor solution;

[0089] (1-2) stirring the nanofiber composite material precursor solution at a rotation speed of 200 rpm for 6 hours, and then ultrasonically treating for 30 minutes to obtain a nanofiber composite material carrier solution;

[0090] (1-3) The nanofiber composite carrier solution was sucked by a needle tube for electrospinning. During electrospinning, the voltage was +15 kV, the solution flow rate was 0.1 mm / min, and the distance between the needle and the receiver was 4 cm. After electrospinning, the membrane was freeze-dried under vacuum for 9 h to obtain a formed nanofiber composite carrier;

[0091] (2) Preparation of molecular sieve composite nanofiber materials with molecular sieve grown on the surface

[0092] (2-1) The nanofiber composite material carrier is placed in a muffle furnace and calcined at 550°C for 6 hours in an air atmosphere to form a porous oxide film on its surface. The oxidized carrier is soaked in a 0.5wt% polyhydroxypropyl dimethyl ammonium chloride solution for 30 minutes, then washed three times with 0.1mol / L ammonia water, and dried at room temperature. Subsequently, the above substances are mixed according to the molar ratio of TEOS, TPAOH, H2O and EtOH of 1:0.36:20:6 to obtain a synthetic solution, and the synthetic solution is poured into a 50mL polytetrafluoroethylene-lined stainless steel reactor, crystallized at 150°C for 18 hours, and the reactor is taken out and quickly cooled with cold water. The obtained seed solution is centrifuged and purified four times until pH = 7 to obtain seed crystals. The obtained seed crystals were added into deionized water to prepare a 2 wt% solution, and the pH value was adjusted to 10 with ammonia water to obtain a seed crystal solution; the carrier modified by the cationic polymer solution was placed in the seed crystal solution and soaked for 1 hour, and then the carrier after adsorbing the seed crystals was washed with 0.1 mol / L ammonia water and dried for use.

[0093] (2-2) The above substances are mixed in a molar ratio of SiO2, TPAOH, Al2O3 and H2O of 1:0.112:0.010:111 to prepare a secondary growth solution, and the secondary growth solution is poured into a 200 mL polytetrafluoroethylene-lined stainless steel reactor. The carrier after adsorbing the seed crystals is then placed vertically in the reactor and crystallized at 150°C for 18 h. The reactor is taken out and quickly cooled with cold water. The obtained molecular sieve membrane sample is washed with deionized water, dried at 100°C, and finally heated to 500°C at a rate of 1°C / min in a muffle furnace, calcined for 4 h, and then cooled to room temperature at the same rate to remove the organic template to obtain a ZSM-5 molecular sieve composite nanofiber material.

[0094] (3) Hydrothermal synthesis method for loading rare earth ions

[0095] (3-1) Take the ZSM-5 molecular sieve composite nanofiber material and immerse it in 2.5 mol / L NaOH solution and let it stand for 24 hours. Then take it out and immerse it in clean water, shake it for 10 minutes and take it out, rotate at 200 rpm, repeat three times, dry it with paper, and dry it at 60°C for 12 hours.

[0096] (3-2) The dried ZSM-5 was placed in 200 mL of 0.5 mol / L La(NO3)3 solution, and shaken at 80°C at 165 rpm for 24 h. Urea was then added to the solution (urea:La=80:1). The reactor was sealed and shaken at 80°C at 165 rpm for 12 h. After being taken out, it was washed with clean water (the cleaning process was the same as (3-1)), and dried at 60°C to obtain a lanthanide-loaded molecular sieve composite nanofiber material.

[0097] The lanthanide-loaded molecular sieve composite nanofiber material prepared in this embodiment is a lanthanide-loaded ZSM-5 molecular sieve composite nanofiber material, and the loaded active component is lanthanum carbonate, which is used to adsorb phosphate in water. The adsorption conditions are pH = 5.5, initial phosphate concentration = 200 mg / L, temperature = 30°C, and adsorbent dosage = 2 g / L. Under these conditions, the adsorption capacity is 74.3 mg-PO4 3- / g.

[0098] Example 3

[0099] A method for preparing a lanthanide-loaded molecular sieve composite nanofiber material comprises the following steps:

[0100] (1) Preparation of nanofiber composite carrier

[0101] (1-1) Weighing 15 g of polyacrylonitrile, measuring 100 mL of N,N-dimethylacetamide, stirring and dissolving the polyacrylonitrile in the N,N-dimethylacetamide to prepare a nanofiber composite material precursor solution;

[0102] (1-2) stirring the nanofiber composite material precursor solution at a rotation speed of 200 rpm for 6 hours, and then ultrasonically treating for 30 minutes to obtain a nanofiber composite material carrier solution;

[0103] (1-3) The nanofiber composite material carrier solution was sucked by a needle tube for electrospinning. During the electrospinning, the voltage was +10 kV, the solution flow rate was 0.1 mm / min, and the distance between the needle and the receiver was 4 cm. After electrospinning, the membrane was freeze-dried under vacuum for 9 h to obtain a formed nanofiber composite material carrier;

[0104] (2) Preparation of molecular sieve composite nanofiber materials with molecular sieve grown on the surface

[0105] (2-1) The nanofiber composite material carrier is placed in a muffle furnace and calcined at 550°C for 6 hours in an air atmosphere to form a porous oxide film on its surface. The oxidized carrier is soaked in a 0.5wt% polyhydroxypropyl dimethyl ammonium chloride solution for 30 minutes, then washed three times with 0.1mol / L ammonia water, and dried at room temperature. Subsequently, the above substances are mixed in a molar ratio of TEOS, TPAOH, H2O and EtOH of 1:0.36:40:8 to obtain a synthetic solution, and the synthetic solution is poured into a 50mL polytetrafluoroethylene-lined stainless steel reactor, crystallized at 150°C for 12 hours, and the reactor is taken out and quickly cooled with cold water. The obtained seed solution is centrifuged and purified four times until pH = 7 to obtain seed crystals. The obtained seed crystals were added into deionized water to prepare a 2 wt% solution, and the pH value was adjusted to 10 with ammonia water to obtain a seed crystal solution; the carrier modified by the cationic polymer solution was placed in the seed crystal solution and soaked for 1 hour, and then the carrier after adsorbing the seed crystals was washed with 0.1 mol / L ammonia water and dried for use.

[0106] (2-2) The above substances are mixed in a molar ratio of SiO2, TPAOH, Al2O3 and H2O of 1:0.112:0.0118:111 to prepare a secondary growth solution, and the secondary synthesis solution is poured into a 200 mL polytetrafluoroethylene-lined stainless steel reactor. The carrier after adsorbing the seed crystals is then placed vertically in the reactor and crystallized at 150°C for 12 h. The reactor is taken out and quickly cooled with cold water. The obtained molecular sieve membrane sample is washed with deionized water, dried at 100°C, and finally heated to 500°C at a rate of 1°C / min in a muffle furnace, calcined for 4 h, and then cooled to room temperature at the same rate to remove the organic template to obtain a ZSM-5 molecular sieve composite nanofiber material.

[0107] (3) Hydrothermal synthesis method for loading rare earth ions

[0108] (3-1) Take the ZSM-5 molecular sieve composite nanofiber material and immerse it in 2.5 mol / L NaOH solution and let it stand for 24 hours. Then take it out and immerse it in clean water, shake it for 10 minutes and take it out, rotate at 200 rpm, repeat three times, dry it with paper, and dry it at 60°C for 12 hours.

[0109] (3-2) The dried ZSM-5 was placed in 200 mL of 0.8 mol / L La(NO3)3 solution, and shaken at 80°C at 165 rpm for 24 h. Urea was then added to the solution (urea:La=80:1). The reactor was sealed and shaken at 80°C at 165 rpm for 12 h. After being taken out, it was washed with clean water (the cleaning process was the same as (3-1)), and dried at 60°C to obtain a lanthanide-loaded molecular sieve composite nanofiber material.

[0110] The lanthanide-loaded molecular sieve composite nanofiber material prepared in this embodiment is a lanthanide-loaded ZSM-5 molecular sieve composite nanofiber material, and the loaded active component is lanthanum carbonate, which is used to adsorb phosphate in water. The adsorption conditions are pH = 5.5, initial phosphate concentration = 200 mg / L, temperature = 30°C, and adsorbent dosage = 2 g / L. Under these conditions, the adsorption capacity is 75.0 mg-PO4 3- / g.

[0111] Comparative Example 1

[0112] (1) Preparation of nanofiber composite carrier

[0113] (1-1) Weighing 10 g of polyacrylonitrile, measuring 100 mL of N,N-dimethylacetamide, stirring and dissolving the polyacrylonitrile in the N,N-dimethylacetamide to prepare a nanofiber composite material precursor solution;

[0114] (1-2) stirring the nanofiber composite material precursor solution at a rotation speed of 200 rpm for 6 hours, and then ultrasonically treating for 30 minutes to obtain a nanofiber composite material carrier solution;

[0115] (1-3) The nanofiber composite material carrier solution was sucked by a needle tube for electrospinning. During electrospinning, the voltage was +10 kV, the solution flow rate was 0.1 mm / min, and the distance between the needle and the receiver was 4 cm. After electrospinning, the membrane was freeze-dried under vacuum for 9 h to obtain a formed nanofiber composite material carrier;

[0116] (2) Hydrothermal synthesis method for loading rare earth ions

[0117] (2-1) Take the nanofiber composite material carrier and immerse it in 2.5 mol / L NaOH solution and let it stand for 24 hours. Take it out and immerse the ZSM-5 molecular sieve composite nanofiber material in clean water, shake it for 10 minutes and then take it out, rotate at 200 rpm, repeat the washing process three times, absorb the water with paper, and dry it at 60°C for 12 hours.

[0118] (2-2) The dried ZSM-5 molecular sieve composite nanofiber material was placed in 200 mL of 0.2 mol / L La(NO3)3 solution, and shaken at 165 rpm at 80°C for 24 h. Urea was then added (urea:La=80:1, molar ratio, the same below). The reactor was sealed and shaken at 165 rpm at 80°C for 12 h. The material was taken out and washed with clean water, and then dried at 60°C.

[0119] The nanofiber material prepared in this comparative example is used to adsorb phosphate in water. The adsorption conditions are pH = 5.5, initial phosphate concentration = 200 mg / L, temperature = 30°C, and adsorbent dosage = 2 g / L. Under these conditions, the adsorption capacity is 16.2 mg-PO4 3- / g.

[0120] Comparative Example 2

[0121] (1) Preparation of molecular sieves

[0122] (1-1) TEOS, TPAOH, H2O and EtOH were mixed in a molar ratio of 1:0.36:10:2 to obtain a synthetic solution, which was poured into a 50 mL polytetrafluoroethylene-lined stainless steel reactor and crystallized at 150°C for 24 hours. The reactor was taken out and quickly cooled with cold water, and the obtained seed solution was purified by centrifugation four times until the pH value was 7 to obtain seed crystals.

[0123] (2-2) SiO2, TPAOH, Al2O3 and H2O were mixed in a molar ratio of 1:0.112:0.005:111 to prepare a secondary growth solution, which was poured into a 200 mL polytetrafluoroethylene-lined stainless steel reactor. The seed crystals were then placed in the reactor and crystallized at 150°C for 24 h. The reactor was taken out and quickly cooled with cold water. The obtained molecular sieve was washed with deionized water, dried at 100°C, and finally heated to 500°C at a rate of 1°C / min in a muffle furnace, calcined for 4 h, and then cooled to room temperature at the same rate to remove the organic template to obtain a ZSM-5 molecular sieve material.

[0124] (2) Hydrothermal synthesis method for loading rare earth ions

[0125] (2-1) Take the ZSM-5 molecular sieve and immerse it in 2.5 mol / L NaOH solution and let it stand for 24 hours. Take it out and immerse it in clean water. Shake it for 10 minutes and then take it out. Repeat the washing process three times at a speed of 200 rpm. Dry it with paper and dry it at 60°C for 12 hours.

[0126] (2-2) The dried molecular sieve was placed in 200 mL of 0.2 mol / L La(NO3)3 solution, and shaken at 80°C at 165 rpm for 24 h. Urea was then added (urea:La=80:1, molar ratio, the same below). The reactor was sealed and shaken at 80°C at 165 rpm for 12 h. After being taken out, it was washed with clean water (the cleaning process was the same as (3-1)), and dried at 60°C to obtain a lanthanide-loaded molecular sieve material.

[0127] The lanthanide-loaded molecular sieve material prepared in this comparative example is used to adsorb phosphate in water. The adsorption conditions are pH = 5.5, initial phosphate concentration = 200 mg / L, temperature = 30°C, and adsorbent dosage = 2 g / L. Under these conditions, the adsorption capacity is 56.0 mg-PO4 3- / g.

[0128] Comparative Example 3

[0129] TEOS, TPAOH, H2O and EtOH were mixed in a molar ratio of 1:0.36:10:2 to obtain a synthetic solution, which was poured into a 50 mL polytetrafluoroethylene-lined stainless steel reactor and crystallized at 150°C for 24 hours. The reactor was taken out and quickly cooled with cold water, and the obtained seed solution was centrifuged and purified four times until the pH was 7 to obtain seed crystals.

[0130] The above substances are mixed to prepare a secondary growth solution according to the molar ratio of SiO2, TPAOH, Al2O3 and H2O of 1:0.112:0.005:111, and the secondary growth solution is poured into a 200mL polytetrafluoroethylene-lined stainless steel reactor, and then the seed crystals are placed in the reactor, crystallized at 150°C for 24h, and the reactor is taken out and quickly cooled with cold water. The obtained molecular sieve is washed with deionized water, dried at 100°C, and finally heated to 500°C at a rate of 1°C / min in a muffle furnace, calcined for 4h, and then cooled to room temperature at the same rate to remove the organic template to obtain a ZSM-5 molecular sieve material. The molecular sieve material prepared in this embodiment is used to adsorb phosphates in water. The adsorption conditions are pH = 5.5, initial phosphate concentration = 200mg / L, temperature = 30°C, and adsorbent dosage = 2g / L. Under these conditions, the adsorption capacity is 32.0mg-PO4 3- / g.

[0131] In summary, the method of the present invention is simple, the prepared material can effectively reduce the bed pressure drop and enhance mass transfer and heat transfer, and the molecular sieve and the nanofiber carrier have a strong interaction, which effectively reduces the leaching rate of the molecular sieve. The molecular sieve grows uniformly on the surface of the nanofiber composite material, and the molecular sieve is loaded with lanthanide, which can effectively improve the adsorption reaction efficiency.

[0132] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A method for preparing a lanthanide-loaded molecular sieve composite nanofiber material, characterized in that: The following steps are involved: (1) mixing polyacrylonitrile and N,N-dimethylacetamide to prepare a nanofiber composite material precursor solution; (2) stirring the nanofiber composite material precursor solution and then ultrasonicating it to obtain a nanofiber composite material carrier solution; (3) obtaining a nanofiber composite material carrier by electrospinning and drying; (4) calcining the dried nanofiber composite material carrier in an air atmosphere, soaking and modifying the calcined nanofiber composite material carrier with a cationic polymer solution, and washing with ammonia water; (5) placing the nanofiber composite material carrier washed with ammonia water in a seed solution and immersing it, and then washing it with ammonia water; (6) mixing the material obtained in step (5) with a secondary growth liquid for crystallization, rapidly cooling with water after the crystallization is completed, and obtaining a molecular sieve composite nanofiber material by washing, drying and calcining; (7) immersing the molecular sieve composite nanofiber material in an alkaline solution, then washing it by shaking, and drying it to obtain a pretreated molecular sieve composite nanofiber material; (8) mixing the pretreated molecular sieve composite nanofiber material with a lanthanum nitrate solution, shaking the reaction under constant temperature conditions, adding urea, and obtaining the lanthanum-loaded molecular sieve composite nanofiber material by a hydrothermal synthesis method; In step (4), the cationic polymer solution is a polyhydroxypropyl dimethyl ammonium chloride solution; In step (5), the seed solution is prepared by mixing TEOS, TPAOH, H2O and EtOH in a molar ratio of 1:0.36:(10-40):(0-8) to obtain the seed solution, and the molar number of EtOH is not 0.

2. The method for preparing the lanthanide-loaded molecular sieve composite nanofiber material according to claim 1, characterized in that: In step (1), the mass volume ratio of polyacrylonitrile and N,N-dimethylacetamide is (5-20):100 mL.

3. The method for preparing the lanthanide-loaded molecular sieve composite nanofiber material according to claim 1, characterized in that: In step (2), the stirring rate is 100 to 300 rpm and the time is 4 to 10 hours; The ultrasonic time is 20 to 60 minutes.

4. The method for preparing the lanthanide-loaded molecular sieve composite nanofiber material according to claim 1, characterized in that: In step (3), the electrospinning conditions are: voltage of 6 to 15 kV, solution flow rate of 0.05 to 0.5 mm / min, and the distance between the needle and the receiver of 3 to 10 cm; The drying is freeze-drying under vacuum for 8 to 12 hours.

5. The method for preparing the lanthanide-loaded molecular sieve composite nanofiber material according to claim 1, characterized in that: In step (4), the calcination temperature is 400-600° C. and the calcination time is 3-8 hours; The soaking time is 10 to 60 minutes; The concentration of the ammonia water is 0.05-0.5 mol / L.

6. The method for preparing the lanthanide-loaded molecular sieve composite nanofiber material according to claim 1, characterized in that: In step (6), the secondary growth solution is prepared by mixing SiO2, TPAOH, Al2O3 and H2O in a molar ratio of 1:0.112:(0-0.118):111 to obtain the secondary growth solution, wherein the molar number of Al2O3 is not 0; The crystallization temperature is 50-200°C; The calcination temperature is 300-1000° C., the heat preservation time is 2-6 hours, and the heating rate and cooling rate are both 0.5-2° C. / min.

7. The method for preparing the lanthanide-loaded molecular sieve composite nanofiber material according to claim 1, characterized in that: In step (8), the molar ratio of urea to lanthanum in the lanthanum nitrate solution is (60-100):

1.

8. A lanthanide-loaded molecular sieve composite nanofiber material, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 7.

9. Use of the lanthanide-loaded molecular sieve composite nanofiber material according to claim 8 in a fixed bed adsorbent.

Citation Information

Patent Citations

  • Preparation method of fiber composite molecular sieve membrane VOCs treatment catalyst

    CN111841625A

  • Lanthanum-doped ordered mesoporous molecular sieve for environmental remediation as well as preparation method and application of lanthanum-doped ordered mesoporous molecular sieve

    CN113457618A